2015
DOI: 10.1111/eci.12417
|View full text |Cite
|
Sign up to set email alerts
|

Repeated implantation failure: a new potential treatment option

Abstract: The current findings support a possible role for the intrauterine administration of autologous CRH-treated PBMC in treating women with RIF. Further randomized controlled trials are needed to investigate the efficacy of this intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 40 publications
0
20
0
1
Order By: Relevance
“…After the implantation, the embryo suppresses this response and prevents the rejection [40]. The deregulation of expression pattern of CRH was associated with unfavorable reproductive outcomes as well as chronic endometrium-derived inflammatory disorders, such as endometriosis and adenomyosis [41]. Positive outcome was found after the intrauterine administration of autologous peripheral blood mononuclear cells (PBMCs) [41] especially when pretreated with corticotropin-releasing hormone that acts by regulating apoptosis of activated T-lymphocytes at the implantation site [42].…”
Section: Endometriummentioning
confidence: 99%
See 1 more Smart Citation
“…After the implantation, the embryo suppresses this response and prevents the rejection [40]. The deregulation of expression pattern of CRH was associated with unfavorable reproductive outcomes as well as chronic endometrium-derived inflammatory disorders, such as endometriosis and adenomyosis [41]. Positive outcome was found after the intrauterine administration of autologous peripheral blood mononuclear cells (PBMCs) [41] especially when pretreated with corticotropin-releasing hormone that acts by regulating apoptosis of activated T-lymphocytes at the implantation site [42].…”
Section: Endometriummentioning
confidence: 99%
“…The deregulation of expression pattern of CRH was associated with unfavorable reproductive outcomes as well as chronic endometrium-derived inflammatory disorders, such as endometriosis and adenomyosis [41]. Positive outcome was found after the intrauterine administration of autologous peripheral blood mononuclear cells (PBMCs) [41] especially when pretreated with corticotropin-releasing hormone that acts by regulating apoptosis of activated T-lymphocytes at the implantation site [42]. The results of eight studies showed that intrauterine administration of activated autologous peripheral blood mononuclear cells prior to embryo transfer improves the reproductive outcomes in women with repeated implantation failure [43].…”
Section: Endometriummentioning
confidence: 99%
“…With the aim of provoking an immune reaction, several efforts have been made by transferring autologous peripheral blood mononuclear cells (PBMCs) in the uterine cavity prior to embryo transfer. PBMCs have been transferred either unstimulated or stimulated by priming the PBMCs with immunomodulatory agents [47,48]. In this context, HCG was the first agent to be used for PBMCs’ activation [48].…”
Section: The Clinical Impact Of Intrauterine Administration Of Hcgmentioning
confidence: 99%
“…Though in vitro fertilization (IVF) success is generally limited to 30% depending on Indeed, with special interest on immunology of reproduction, Yoshioka et al [23] 20 was the first team which could to realize immunotherapy for patients with repeated IVF 21 failures based on intrauterine administration of peripheral blood mononuclear cells 22 (PBMC). Then, several studies developed this novel approach with some modifications 23 on PBMC preparation protocol, including fresh or frozen cycles, embryo day 3 or 24 blastocyst transfer, patients with at least 2, 3 or 4 RIF in order to improve significantly 25 clinical outcomes and decrease the miscarriage rates [22,24,25]. 26 Furthermore, PBMC immunotherapy could to be efficient for some RPL cases and 27 avoiding miscarriages [22,26,27] despite lack of clear definition toward RIF and 28 RPL [28].…”
Section: Introductionmentioning
confidence: 99%
“…108 Yoshioka et al were the pioneers in this approach application while the research teams' 109 followers could to involve some technical modifications in PBMC preparation 110 protocol [23]. Some could to prove the efficiency of hCG supplementation on PBMC 111 culture for 72h [22,24] or trying to minimize latter to 24h [26,27,34] while others were 112 more focused on the efficiency of CRH [25]. All these technical adaptations were 113 occurred in order to enhance at maximum the function of PBMC and their cytokines 114 secretions to activate thereafter the maternal immune system into endometrium after an 115 intrauterine administration and be ready for embryo implantation.…”
mentioning
confidence: 99%